Durability and Dimensional Stability Assessment of Chemically Treated Harvested Bamboo (Bambusa balcooa Roxb). - Borthakur, Runumee D.; Gogoi, P. K.; Borah, R. K. (Indian Forester, 2018)
The present experiment was carried out to study the durability and dimensional stability of the chemically treated bamboo (Bambusa balcooa). The efficacy of the preservative chemicals for the treatment of bamboo samples was evaluated in ground contact against termite and fungus. The bamboo samples treated with boric acid (BA), copper acetate (CA), phthalic anhydride (PA), sodium salt of triet Helen tetramine dithiocarbamate (triendtc) and kerosene showed higher dimensional stability efficiency in terms of anti shrink efficiency (ASE), bulk coefficient (BC) and weight percent gain (WPG). The strength properties such as modulus of rupture (MOR) and modulus of elasticity (MOE) of treated bamboo samples showed higher values than the untreated bamboo sample. The thermal behavior of the treated and untreated samples were studied using thermogravemetric (TG) and differential thermogravemetric (DTG) techniques and found that the treated samples were thermally more stable than the untreated one. The treated bamboo samples could resist termite and fungal attack which extend the service life.